Biologi Penggerek Batang Jagung Ostrinia furnacalis Gueneé yang diberi Pakan Buatan - ARIF MUKHTAR HASBI; RIKA RAFFIUDIN; I MADE SAMUDRA (Departemen Biologi, Institut Pertanian Bogor, 2016)
Ostrinia furnacalis is a corn stem-borer that develops complete metamorphosis and all stages in life cycle in corn. This research was aimed to examine several biology aspects of O. furnacalis such as life cycle, egg incubaton period, egg fertility, female fecundity, longevity of imago, and copulation time on artificial diet, based on the previous study. The results of the observations showed that the life cycle of artificial-diet-given O. furnacalis was between 27-34 days range. Female fecundity was 16-452 eggs with fertility rate of 61,97% and 3-5 days renge of egg incubation period. Longevity of imago was between 6-11 days range, and the longevity was longer in female compared to the male. The imago of O. furnacalis copulate on 0-3 days after emerge from pupae and the highest number in on the day 1. Copulation time was occurred at 3-8 hour after scotophase commenced and the highest was at third hour. The artificial diet used in this research can be used for O. furnacalis mass rearing purpose and performed shorter length of egg stage until pupal stage compared to mass rearing with natural diet.